USING GENRE BASED APPROACH IN ONLINE LEARNING TO IMPROVE STUDENTS’ WRITING SKILL IN WRITING ANALYTICAL EXPOSITION TEXT - Azhari Yunus (STKIP Al Hikmah Surabaya, 2023)
This study is aimed to finding out whether there is a significant difference towards students’ writing ability who are taught by process genre-based approach and those who are taught by using non-PGBA learning through online learning. The result of this study showed that (1) there were significant effects of process genre-based approach through online learning on students’ writing skills in analytical exposition text. The result of the pre-test to post-test difference test using the Independent T-test generated the Asymp value. Sig (2 – tailed) is 0.001 (p < 0.05), so, that H0 is rejected and Hi is accepted, it continue with the result of the effect size test using Pearson correlation r, and obtained r = 0.411 (16.94%) and categorized in medium effect. (2) The aspects of writing in the experimental group (PGBA); The percentage of Organization (16.08%) and Spelling (81.3%) scaled with excellent criteria. Meanwhile 4 from 6 aspect; for the Idea and Development is (23.50%), Vocabulary (11.91%), Sentence Structure (14.83%), Capitalization and Punctuation (7.25%) have scaled into good criteria. Then, the difference score (23%). The difference score here figures out the students’ scores not achieved maximally.